Percepção socioambiental como instrumento de análise para implantação do ecoturismo em unidades de conservação - Cândido, Vinícius Alves (2017)
Protecd Area are areas destined to the preservation and conservation of biodiversity in order to contribute with the environment and society. The environmental perception of local community can be used as socioenvironmental indicator to understand the relation of the residents with the environment, thus allowing us to stipulate strategies for environmental planning and management. The different segments of tourism activities are considered compatible with the objectives of conservation and with the generation of employment and income in Protecd Area. In this context, the objective of this study was to verify the socioenvironmental feasibility of ecotourism in a Park still officially closed to activity, from the perspective of the local community of the area, as well as the acknowledgement of vocations, potentials, participation and expectations regarding the activity. The case study is based on a descriptive approach, with qualitative analysis, using content analysis for data treatment. The studied area is located in the municipality of Itamonte, southern Minas Gerais, Brazil, in the Vargem Grande neighbourhood, near the Serra do Papagaio State Park. The research sought specific individuals based on their experience or knowledge of the theme, by means of the snowball sampling for selecting key actors. The collection of the information for the research was done by means of the application of semi-structured questionnaires containing thirteen guide questions. The data were treated with theme analysis. Expropriation was the most consistent complaint made by the residents. The solution found by two families was tourism hosting. The community does not receive training. The lack of communication cases insecurity concerning the destination of the families. The participation of the local community on the management of the Serra do Papagaio State Park is done by means of Advisory Council, however, this is not considered an effective tool to solve the issues found by the community. The residents showed interest in the tourism activity, however, they show no knowledge regarding ecotourism, lacking the vocations, potentials and expectations of field.